Energy transfer in diiodoBodipy-grafted upconversion nanohybrids. Issue 1 (8th December 2015) - Francés-Soriano, Laura; Liras, Marta; Kowalczyk, Agnieszka; Bednarkiewicz, Artur; González-Béjar, Maria; Pérez-Prieto, Julia
Abstract : The Yb 3+ excited state can decay via two competitive energy transfer processes: sensitization of IBDP after absorption of a second NIR photon and population of Er 3+ excited states. Abstract : Steady-state and time-resolved emission studies on nanohybrids consisting of NaYF4 :Yb, Er and a diiodo-substituted Bodipy (UCNP–IBDP) show that the Yb 3+ metastable state, formed after absorption of a near-infrared (NIR) photon, can decay via two competitive energy transfer processes: sensitization of IBDP after absorption of a second NIR photon and population of Er 3+ excited states.